Design MicroServer Framework Library with Swoole for Real-time Application Development - Mufid, Muhammad Robihul; Pratama, Yogi; Fariza, Arna; Mawaddah, Saniyatul; Ikawati, Yunia; Aditama, Darmawan; Tahir, Muhlis (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2024)
The PHP programming language is known as a synchronous programming language because the request execution model is carried out sequentially and is very easy to apply in creating systems with simple scenarios. With this model, there will be many challenges in developing real-time applications because sequential model execution can cause bottlenecks because it initializes threads on each request which causes more resource consumption, making it less suitable for handling I/O (Input/Output) operations on an Intense scale. This study aims to implement an asynchronous model in PHP by developing a Xel Async framework that can be used as a foundation for creating micro servers using the Swoole extension. This study will explain the framework developed starting from system modeling, component design, abstraction design that focuses on response time, throughput, and efficient and effective resource usage in handling heavy traffic. To see the performance of the framework developed, an analysis was carried out with other frameworks such as Express Js. And the results show that the Xel Async framework offers significant performance carried out on benchmark tests for 100, 250, 500, 1000 connections and is able to produce a better amount of latency. In addition, an analysis was also carried out for throughput on Xel Async and Express Js, which also produced better performance than Express Js